TRADE MARKS IN EUROPE AND THEIR COMPETITIVENESS - V. Nikolova-Minkova (Trakia Journal of Sciences)
The development of modern business depends to a large extent on consumers and their choice. This is a reason for the companies to compete in creating powerful trademarks through which to attract more consumers and gain a greater market share. Objects of scientific interest in this study are the formed image of the trademarks and the degree of consumer loyalty to them that affects the value of the brands. The purpose of the present study is to explore the leading European brands and to analyze the conditions for developing their competitiveness. In this regard, by applying empirical methods of research (study, comparison and analysis of expert assessments), the paper clarifies the essence of the trademarks and brands and considers the formation of their value based on the image built. The results of the methods used reveal the most valuable for European trademarks, as well as the prerequisites for forming consumer loyalty to them. In conclusion, recommendations are made to increase the competitiveness of brands, which can contribute to increasing consumer loyalty.